Exploring the fundamentals of Ni-based superalloy single crystal (SX) alloy design: Chemical composition vs. microstructure. (October 2020) - Horst, O.M.; Adler, D.; Git, P.; Wang, H.; Streitberger, J.; Holtkamp, M.; Jöns, N.; Singer, R.F.; Körner, C.; Eggeler, G.
Abstract: The present work contributes to a better understanding of the basic assumptions and principles behind the design of Ni-based single crystal superalloys (SXs). For this purpose, we cast and heat-treat four SXs and compare their creep performances: ERBO/1 (with Re) and three ERBO/15 variants (no Re but increased levels of Ti, Mo and W). We show that Re can be replaced by other elements without losing creep strength. To come to this conclusion one has to consider both, alloy composition and microstructure. We analyze the mechanical, microstructural and chemical results (creep rates, γʼ-volume fractions, average γʼ-particle sizes, average γ-channel widths and the chemistry of γ- and γʼ-phases) obtained for ERBO/15 and its two leaner variants (less Mo: ERBO/15-Mo and less W: ERBO/15-W). ERBO/15-Mo and ERBO/15-W show higher creep rates than ERBO/15, because they exhibit lower Mo and W concentrations in the γ-channels. This results in higher diffusion rates, accelerated rafting and faster dislocation climb at γ/γʼ-interfaces. Graphical abstract: Unlabelled Image Highlights: A computer aided newly developed Ni-base superalloy without Re outperforms the creep performance of a CMSX-4 type with Re. Adjustment of overall alloy composition and microstructure are equally important for alloy design. The influence of an individual element on creep has to be analyzed by changing the concentration of this and the base element. Reduction of the nominal concentration of Mo or W in the Re-free superalloy results in significantly higher creep rates. These higher creep rates can be explained by lower concentrations of Mo or W in the γ-channels.